2020
DOI: 10.1021/acs.joc.9b03370
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Meayamycin B

Abstract: Meayamycin B is currently the most potent modulator of the splicing factor 3b subunit 1 and used by dozens of research groups. However, current supply for this natural product analogue is limited because of the lengthy synthetic scheme. Here, we report a more concise, more cost-effective, and greener synthesis of this compound by developing and employing a novel asymmetric reduction of a prochiral enone to afford an allylic alcohol with high enantioselectivity. In addition to this reaction, this synthesis high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…25,26 Examples include the preparation of mucocin, amphidinol 3 and the formation of the E ring in maitotoxin, as well as the botcinins, and more recently in the total synthesis of meayamycin B, illustrating the widespread value of the method (Scheme 3). [27][28][29][30][31][32] In 1997, Nakata and co-workers reported that introduction of a styryl group adjacent to the epoxide provided greater stabilisation in the 6-endo transition state compared with the alkenic epoxides. 33,34 Treatment of trans-epoxides containing a styryl group with either acid or base generated THP products in excellent yield, but improved stereocontrol was achieved using NaH (entries 1 and 2, Table 1).…”
Section: Reviewmentioning
confidence: 99%
“…25,26 Examples include the preparation of mucocin, amphidinol 3 and the formation of the E ring in maitotoxin, as well as the botcinins, and more recently in the total synthesis of meayamycin B, illustrating the widespread value of the method (Scheme 3). [27][28][29][30][31][32] In 1997, Nakata and co-workers reported that introduction of a styryl group adjacent to the epoxide provided greater stabilisation in the 6-endo transition state compared with the alkenic epoxides. 33,34 Treatment of trans-epoxides containing a styryl group with either acid or base generated THP products in excellent yield, but improved stereocontrol was achieved using NaH (entries 1 and 2, Table 1).…”
Section: Reviewmentioning
confidence: 99%
“…After several iterations on the approach, each subunit used to assemble 1 herein is derived from chiral pool starting materials with all 8 chiral centers introduced or controlled by chirality found in inexpensive commercial starting materials (Figure ). The approach provided 1 in a longest linear sequence of 12 steps (22 steps overall), complementary to an improved approach recently disclosed by Koide (11 longest linear sequence, 24 steps overall) …”
mentioning
confidence: 99%
“…Although inspired by Koide’s original synthesis, it is substantially shorter (5 vs 8 steps) and enlists further optimized protocols for overlapping steps. Analogous improvements were independently reported by Koide earlier this year for synthesis of intermediate lactone 12 . Additional subtle improvements are also highlighted herein for the original conversion of 12 to 15 .…”
mentioning
confidence: 99%
See 2 more Smart Citations